Nicotine dependence, its risk indicators, and exhaled carbon monoxide levels among the smokers in Bengaluru, India - P Sugavanesh; K Pushpanjali (Wolters Kluwer Medknow Publications, 2018)
Background: Tobacco is the significant cause of preventable death worldwide. The prevalence of smoking in India is 13.3%. Among the chemical constituents in the cigarette, nicotine is the one most often associated with dependence resulting in increased consumption of them. Studies have proven the dose-dependent relationship of cigarette smoking with lung and oropharyngeal cancer. Hence, assessment of nicotine dependence among the smokers is essential as it influences the tailor-made intervention. Objectives: The objectives of this study were to assess the nicotine dependence and exhaled carbon monoxide (CO) levels among the smokers in Bengaluru. Materials and Methods: A cross-sectional survey was conducted among 396 smokers selected using probability proportional to size sampling technique. Fagerstrom Test for Nicotine Dependence was used to assess the levels of nicotine dependence. Exhaled CO levels were measured using the Smokerlyzer to indicate the nicotine dependence. Results: About 23.7% of the participants had the very low dependence on nicotine. Nearly 26% and 22.5% of the participants had the high and very high dependence on nicotine correspondingly. The number of years of smoking was found as a significant risk indicator for nicotine dependence. Exhaled CO levels were significantly correlated with the nicotine dependence (P = 0.000) indicating it as a marker for nicotine dependence. Conclusion: The high nicotine dependence among the participants warrants effective public health policies to prevent tobacco-related diseases. Considering the risk indicator, the number of years of smoking, smoking cessation programs should target the participants with the habit of continuous smoking with tailor-made interventions to prevent the relapse among them.